Electroplating PC / ABS alloy material easy to coarsen as well as preparation method and application of electroplating PC / ABS alloy material
Through the application of modified polyvinyl alcohol fibers in PC/ABS materials, the problem of low coarse efficiency of electroplating materials is solved, the electroplating performance and mechanical properties are improved, and it is suitable for electroplating materials with high strength requirements.
Patent Information
- Application Number
- CN202411418513.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-10-12
AI Technical Summary
The existing PC/ABS electroplating materials are inefficient during the roughening process, resulting in poor electroplating performance and easily affect material compatibility and mechanical properties when adding PEO resin.
Modified polyvinyl alcohol fibers are modified by maleic anhydride graft to increase the hydrophilicity and compatibility of the material, improve the coarse efficiency, and control the content in the alloy between 1-20 parts to improve the mechanical properties. .
It significantly improves the coarse efficiency and electroplating performance of PC/ABS materials, while maintaining the mechanical strength of the material, and is suitable for electroplating materials application scenarios with high strength requirements.
Smart Images

Figure BDA0005080115330000021 
Figure BDA0005080115330000071 
Figure BDA0005080115330000101
Abstract
Description
Technical Field
[0001] The invention relates to an alloy material with improved electroplating performance, in particular to an electroplated PC / ABS alloy material that is easy to be roughened, and a preparation method and application thereof. Background Art
[0002] With the rapid development of the automobile industry and the increasing demand for lightweight automobiles, electroplated PC / ABS materials are being increasingly widely used in automotive interior and exterior panels, door handles and other parts due to their excellent mechanical properties and the ability to obtain excellent metal effects after electroplating.
[0003] The specific process of electroplating is relatively complicated, mainly including the steps of roughening, reduction, sensitization, activation, degumming, chemical nickel plating, pre-copper plating, nickel plating, chromium plating, etc. Among them, roughening is the key step in the pre-treatment process of electroplating. In the electroplating of PC / ABS materials, the "B" phase butadiene rubber in the ABS material is etched by using chromic acid and concentrated sulfuric acid, so that the surface of the material presents a microscopic rough structure, increasing the contact area between the coating and the plastic substrate. This process gives PC / ABS materials good electroplating properties. However, since PC cannot be electroplated, the electroplating ability of PC / ABS is not as good as that of ABS. At the same roughening temperature, the roughening time of PC / ABS is longer than that of electroplated ABS. Therefore, it is necessary to develop PC / ABS alloys that are easy to roughen to improve the production efficiency of electroplating.
[0004] Patent CN103602053A improves the surface hydrophilicity of PC / ABS materials by adding PEO resin, making roughening easier to occur. However, if the amount of PEO resin added is too low, it will not significantly improve the electroplating performance, and if the amount is too high, it will have a greater impact on the compatibility and mechanical properties of the material, making it difficult to apply to electroplating material application scenarios with high strength requirements. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides an electroplated PC / ABS alloy material that is easy to roughen and a preparation method and application thereof. The electroplated PC / ABS material provided by the present invention has significantly improved roughening efficiency while taking into account the mechanical strength of the material.
[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0007] An easily roughened electroplated PC / ABS alloy material comprises the following components in parts by weight:
[0008]
[0009] The modified polyvinyl alcohol fiber is polyvinyl alcohol fiber grafted with maleic anhydride. Preferably, the mass ratio of the modified raw material, based on the polyvinyl alcohol fiber and maleic anhydride, is (5-7):(3-5).
[0010] The content of modified polyvinyl alcohol fiber in the PC / ABS alloy material is crucial. To ensure the realization of the present invention, the weight portion of the modified polyvinyl alcohol fiber in the system is not less than 1 part, preferably not less than 5 parts, otherwise it is difficult to achieve the effect of improving the roughening efficiency. At the same time, the weight portion of the modified polyvinyl alcohol fiber in the system is required to be not more than 20 parts, preferably not more than 10 parts, otherwise even if the polyvinyl alcohol fiber is modified with maleic anhydride, it will affect the toughness and compatibility of the material, and then the mechanical properties will decrease.
[0011] In some specific examples of the present invention, the polycarbonate is an aromatic polycarbonate and / or an aliphatic polycarbonate, preferably bisphenol A polycarbonate;
[0012] Preferably, the polycarbonate has a melt flow index of 3-65 g / 10 min, preferably 5-50 g / 10 min, and more preferably 7-35 g / 10 min, when tested at 300° C. and 1.2 kg.
[0013] In some specific examples of the present invention, the ABS resin is a terpolymer of acrylonitrile, butadiene and styrene, wherein the mass proportions of the components are: 15-40% acrylonitrile, 10-60% butadiene, and 25-70% styrene.
[0014] In some specific examples of the present invention, the raw material polyvinyl alcohol used for the polyvinyl alcohol fiber has a polymerization degree of 500-2000, an alcoholysis degree of more than 50%, preferably 50-95%, and a water-soluble temperature lower than 60°C, preferably 30-50°C.
[0015] In some specific examples of the present invention, the processing aid is selected from one or more of an antioxidant, a lubricant, a light stabilizer, a heat stabilizer, an antistatic agent, a filler, an antifogging agent, and a light diffuser;
[0016] Preferably, the antioxidant is one or more of hindered phenols, phosphites, thioesters, benzofurans, acryl-modified phenols, and hydroxylamine antioxidants;
[0017] Preferably, the lubricant is one or more of fatty alcohols, metal soaps, fatty acids, fatty acid esters, amide waxes, saturated hydrocarbons, polyolefin waxes and their derivatives, organic silicon and silicone powder, and organic fluorine;
[0018] Preferably, the antioxidant is one or more of hindered phenols, phosphites, thioesters, benzofurans, acryl-modified phenols, and hydroxylamine antioxidants;
[0019] Preferably, the lubricant is one or more of fatty alcohols, metal soaps, fatty acids, fatty acid esters, amide waxes, saturated hydrocarbons, polyolefin waxes and their derivatives, silicone and silicone powders, and organic fluorines;
[0020] Preferably, the light stabilizer is one or more of benzotriazoles, triazines, benzoates, cyanoacrylates, and phenylimidazoles;
[0021] Preferably, the antistatic agent is one or more of phosphoric acid, inorganic semiconductor salt, carbon black, and sodium cellulose sulfate;
[0022] Preferably, the filler is one or more of calcium carbonate, glass fiber, kaolin, silicon dioxide, talc, montmorillonite, diatomaceous earth, barium sulfate, glass microbeads, carbon black, mica, wollastonite, and whiskers;
[0023] Preferably, the light diffuser is one or more of nano barium sulfate, calcium carbonate, silicon dioxide, and organic nano micro-pearl light diffusers.
[0024] The polyvinyl alcohol fiber of the present invention has certain water solubility and hydrophilicity, can be efficiently infiltrated in the process of treating the alloy with the roughening liquid, and quickly forms etching points on the material surface to facilitate electroplating, thereby improving the electroplating performance. Maleic anhydride modification retains its hydrophilicity while grafting the anhydride group during the ABS melt co-extrusion process to improve the system compatibility, making the ABS distribution more uniform and conducive to roughening. In addition, the introduction of the modified polyvinyl alcohol fiber further improves the mechanical strength of the alloy material.
[0025] A method for preparing the electroplated PC / ABS alloy material that is easy to roughen as described above comprises the following steps: mixing polycarbonate, ABS resin, modified polyvinyl alcohol fiber, optional processing aid and initiator, melt extruding, and granulating to obtain the PC / ABS alloy material;
[0026] Preferably, the initiator is a peroxide initiator, preferably one or both of dicumyl peroxide (DCP) and dibenzoyl peroxide (BPO);
[0027] Preferably, the amount of the initiator is 0.2-0.6% of the total mass of the polycarbonate, ABS resin, modified polyvinyl alcohol fiber, and optional processing aids.
[0028] In some specific examples of the preparation method of the present invention, the melt extrusion uses a twin-screw extruder, wherein the barrel temperature is 220-260° C. and the screw speed is 200-600 rpm.
[0029] In some specific examples of the preparation method of the present invention, the preparation method of the modified polyvinyl alcohol fiber is:
[0030] The polyvinyl alcohol fiber, maleic anhydride and an esterification catalyst are mixed in a solvent and reacted;
[0031] Preferably, the reaction temperature is 90-100°C and the reaction time is 8-12h.
[0032] Preferably, the mass ratio of the polyvinyl alcohol fiber to maleic anhydride is (5-7):(3-5).
[0033] In some specific examples of the preparation method of the present invention, the esterification catalyst is selected from one or more of p-toluenesulfonic acid, thionyl chloride, and trifluoromethanesulfonic acid;
[0034] Preferably, the esterification catalyst is used in an amount of 0.1-0.3% of the total mass of the polyvinyl alcohol fiber and maleic anhydride;
[0035] Preferably, the solvent is one or more of DMF, dichloromethane and chloroform.
[0036] After the reaction is completed, the reaction solution is cooled, filtered and dried to obtain the modified polyvinyl alcohol fiber.
[0037] The present invention also provides an application of the easily roughened electroplated PC / ABS alloy material as described above or the easily roughened electroplated PC / ABS alloy material obtained by the method described above in automobile parts.
[0038] The PC / ABS alloy material provided by the present invention has an improved roughening efficiency, and after the ABS is grafted with modified polyvinyl alcohol fibers, it is more evenly dispersed, and can provide a more uniform "B" phase for roughening, thereby improving the electroplating quality. In particular, the scheme of the present invention controls the component content within a certain range. On the basis of the aforementioned improved effects, it not only does not damage the mechanical properties of the alloy material, but also has a certain gain effect on the improvement of mechanical strength. The obtained alloy material is particularly suitable for electroplating material application scenarios with high strength requirements. DETAILED DESCRIPTION
[0039] The present invention is further described below by means of specific examples. The examples described in the present invention are only used to illustrate the present invention and do not limit the scope of the present invention.
[0040] The raw material information in the following examples is as follows:
[0041] PC 2100: Wanhua Chemical Group Co., Ltd., MFR (300℃1.2kg) = 10g / 10min
[0042] PC 2220: Wanhua Chemical Group Co., Ltd., MFR (300℃1.2kg) = 22g / 10min
[0043] ABS (PA757): Chi Mei Company, Taiwan, China, acrylonitrile content 23%, butadiene content 15%, styrene content 62%
[0044] ABS (HR181): Kumho Co., Ltd., South Korea, acrylonitrile content 15%, butadiene content 55%, styrene content 30%
[0045] Maleic anhydride: Shanghai Aladdin Biochemical Technology Co., Ltd.
[0046] Polyvinyl alcohol fiber A: 30-45℃ water soluble, polyvinyl alcohol polymerization degree is 1700, alcoholysis degree is 95%, Shandong Hongsheng New Materials Co., Ltd.
[0047] Polyvinyl alcohol fiber B: 70-90℃ water soluble, polyvinyl alcohol polymerization degree is 1800, alcoholysis degree is 70%, Shandong Hongsheng New Materials Co., Ltd.
[0048] Lubricant PETs: Faji Chemicals (Zhangjiagang) Co., Ltd.
[0049] Antioxidant 1010: Tianjin Lianlong New Materials Co., Ltd.
[0050] Antioxidant 168: Tianjin Lianlong New Materials Co., Ltd.
[0051] Dicumyl peroxide: Shanghai Aladdin Biochemical Technology Co., Ltd.
[0052] p-Toluenesulfonic acid: Shanghai MacLean Biochemical Technology Co., Ltd.
[0053] N,N-Dimethylformamide: Shanghai Aladdin Biochemical Technology Co., Ltd.
[0054] Unless otherwise specified, other raw materials and reagents were purchased from commercial sources.
[0055] In the following embodiments and comparative examples, the performance test methods of PC / ABS alloy materials are shown in Table 1:
[0056] Table 1. Performance test methods
[0057]
[0058] The processing equipment used are:
[0059] Twin-screw extruder, Coperion, model ZSK 26Mc 18, aspect ratio 52, screw diameter 26 cm;
[0060] Injection molding machine, 130-ton KraussMaffei injection molding machine, model KM130-380CX;
[0061] German ZWICK Z010TE universal testing machine;
[0062] German ZWICK HIT25P pendulum impact machine;
[0063] American MTS CMT4104-BZ microcomputer controlled electronic universal testing machine.
[0064] [Example 1]
[0065] 50 g of polyvinyl alcohol fiber A, 50 g of maleic anhydride and 0.3 g of p-toluenesulfonic acid were added to 100 ml of DMF solution, reacted at 90° C. for 8 h, filtered, and dried at 80° C. for 2 h to obtain modified polyvinyl alcohol fiber 1.
[0066] 19g polycarbonate 2220, 70g ABS (PA757), 10g modified polyvinyl alcohol fiber 1 prepared above, 0.3g lubricant PETs, 0.05g antioxidant 168, 0.05g antioxidant 1010 and 0.6g initiator DCP were added to a high mixer and mixed for 5 minutes. The mixed materials were added to the main feed of the twin-screw extruder. The extrusion conditions were: screw speed 200rpm, and the screw temperature was set from the feed port to the head in sections as follows: 220℃, 225℃, 230℃, 235℃, 235℃, 250℃, 250℃, 245℃, 245℃, 240℃, 240℃. After extrusion, granulation was performed to obtain PC / ABS alloy material.
[0067] [Example 2]
[0068] 70 g of polyvinyl alcohol fiber A, 30 g of maleic anhydride and 0.1 g of p-toluenesulfonic acid were added to 100 ml of DMF solution, reacted at 100° C. for 12 h, filtered, and dried at 80° C. for 2 h to obtain modified polyvinyl alcohol fiber 2.
[0069] 79.4g polycarbonate 2100, 15g ABS (HR181), 5g modified polyvinyl alcohol fiber 2 prepared above, 0.3g lubricant PETs, 0.05g antioxidant 168, 0.05g antioxidant 1010 and 0.2g initiator DCP were added to a high mixer and mixed for 5 minutes. The mixed materials were added to the main feed of the twin-screw extruder. The extrusion conditions were: screw speed 600rpm, and the screw temperature was set to 230℃, 235℃, 240℃, 245℃, 250℃, 260℃, 260℃, 255℃, 255℃, 250℃, 250℃ from the feed port to the die head. After extrusion, granulation was performed to obtain PC / ABS alloy material.
[0070] [Example 3]
[0071] 60 g of polyvinyl alcohol fiber A, 40 g of maleic anhydride and 0.2 g of p-toluenesulfonic acid were added to 100 ml of DMF solution, reacted at 95° C. for 10 h, filtered, and dried at 80° C. for 2 h to obtain modified polyvinyl alcohol fiber 3.
[0072] 41g polycarbonate 2100, 50g ABS (HR181), 8g modified polyvinyl alcohol fiber 3 prepared above, 0.4g lubricant PETs, 0.1g antioxidant 168, 0.1g antioxidant 1010 and 0.4g initiator DCP were added to a high mixer and mixed for 5 minutes. The mixed materials were added to the main feed of the twin-screw extruder. The extrusion conditions were: screw speed 400rpm, and the screw temperature from the feed port to the die was set to 235℃, 240℃, 245℃, 250℃, 255℃, 260℃, 255℃, 250℃, 250℃, 250℃, 250℃, 250℃. After extrusion, granulation was performed to obtain PC / ABS alloy material.
[0073] [Example 4]
[0074] 63g polycarbonate 2100, 30g ABS (PA757), 6g modified polyvinyl alcohol fiber 1 prepared in Example 1, 0.4g talcum powder, 0.3g lubricant PETs, 0.05g antioxidant 168, 0.05g antioxidant 1010 and 0.2g initiator DCP were added to a high mixer and mixed for 5 minutes. The mixed materials were added to the main feed of the twin-screw extruder. The extrusion conditions were: screw speed 300rpm, and the screw temperature was set to 220℃, 225℃, 230℃, 235℃, 235℃, 250℃, 250℃, 245℃, 245℃, 240℃, 240℃ from the feed port to the head. After extrusion, granulation was performed to obtain PC / ABS alloy material.
[0075] [Example 5]
[0076] 30g polycarbonate 2220, 60g ABS (HR181), 9g modified polyvinyl alcohol fiber 2 prepared in Example 2, 0.3g lubricant PETs, 0.1g antioxidant 168, 0.1g antioxidant 1010 and 0.5g initiator DCP were added to a high mixer and mixed for 5 minutes. The mixed materials were added to the main feed of the twin-screw extruder. The extrusion conditions were: screw speed 500rpm, and the screw temperature was set to 230℃, 235℃, 240℃, 245℃, 250℃, 260℃, 260℃, 255℃, 255℃, 250℃, 250℃ from the feed port to the die head. After extrusion, granulation was performed to obtain PC / ABS alloy material.
[0077] [Comparative Example 1]
[0078] The PC / ABS alloy material was prepared in substantially the same manner as in Example 1, except that the modified polyvinyl alcohol fiber in the composition raw material was replaced with polyvinyl alcohol fiber A of the same mass.
[0079] [Comparative Example 2]
[0080] The PC / ABS alloy material was prepared in a method substantially the same as that in Example 1, except that the modified polyvinyl alcohol fiber 1 was not added during the preparation process.
[0081] [Comparative Example 3]
[0082] The PC / ABS alloy material was prepared in substantially the same manner as in Example 1, except that the amount of the modified polyvinyl alcohol fiber 1 in the composition raw material was changed to 2 g.
[0083] [Comparative Example 4]
[0084] The PC / ABS alloy material was prepared in a method substantially the same as that in Example 1, except that the modified polyvinyl alcohol fiber 1 in the composition raw material was replaced with a modified fiber prepared by the following method:
[0085] 50 g of polyvinyl alcohol fiber B, 50 g of maleic anhydride and 0.3 g of p-toluenesulfonic acid were added to 100 ml of DMF solution, reacted at 90° C. for 8 h, filtered, and dried at 80° C. for 2 h to obtain modified fiber.
[0086] The PC / ABS alloy materials prepared in each embodiment and comparative example were processed into strips in an injection molding machine, and the temperatures of each section of the screw were set to 230° C., 240° C., 250° C., and 240° C. The performance tests in Table 2 were performed on each injection molded strip, as follows.
[0087] Table 2. Performance test results
[0088]
[0089]
[0090] The above is only a preferred embodiment of the present invention. It should be pointed out that ordinary technicians in this field can make several improvements and supplements without departing from the method of the present invention. These improvements and supplements should also be regarded as the scope of protection of the present invention.
Claims
1. An electroplated PC / ABS alloy material that is easy to roughen. It is characterized in that According to parts by weight, it comprises the following components: The modified polyvinyl alcohol fiber is polyvinyl alcohol fiber grafted with maleic anhydride. Preferably, the mass ratio of the modified raw material, based on the polyvinyl alcohol fiber and maleic anhydride, is (5-7):(3-5).
2. The easily roughened electroplated PC / ABS alloy material according to claim 1, It is characterized in that The polycarbonate is an aromatic polycarbonate and / or an aliphatic polycarbonate, preferably bisphenol A polycarbonate; Preferably, the polycarbonate has a melt flow index of 3-65 g / 10 min, preferably 5-50 g / 10 min, and more preferably 7-35 g / 10 min, when tested at 300° C. and 1.2 kg.
3. The easily roughened electroplated PC / ABS alloy material according to claim 1, It is characterized in that The ABS resin is a terpolymer of acrylonitrile, butadiene and styrene, wherein the mass proportions of the components are: 15-40% acrylonitrile, 10-60% butadiene and 25-70% styrene.
4. The easily roughened electroplated PC / ABS alloy material according to any one of claims 1 to 3, It is characterized in that The raw material polyvinyl alcohol used in the polyvinyl alcohol fiber has a polymerization degree of 500-2000, an alcoholysis degree of 50% or more, preferably 50-95%, and a water-soluble temperature of less than 60°C, preferably 30-50°C.
5. The easily roughened electroplated PC / ABS alloy material according to any one of claims 1 to 4, It is characterized in that The processing aid is selected from one or more of antioxidants, lubricants, light stabilizers, heat stabilizers, antistatic agents, fillers, antifogging agents, and light diffusers.
6. A method for preparing the easily roughened electroplated PC / ABS alloy material as claimed in any one of claims 1 to 5, It is characterized in that The following steps are involved: The polycarbonate, ABS resin, modified polyvinyl alcohol fiber, optional processing aid and initiator are mixed, melt-extruded, and granulated to obtain a PC / ABS alloy material; Preferably, the initiator is a peroxide initiator, preferably one or both of dicumyl peroxide and dibenzoyl peroxide; Preferably, the amount of the initiator is 0.2-0.6% of the total mass of the polycarbonate, ABS resin, modified polyvinyl alcohol fiber, and optional processing aids.
7. The easily roughened electroplated PC / ABS alloy material according to claim 6, It is characterized in that The melt extrusion uses a twin-screw extruder, wherein the barrel temperature is 220-260° C. and the screw speed is 200-600 rpm.
8. The easily roughened electroplated PC / ABS alloy material according to claim 6 or 7, It is characterized in that The preparation method of the modified polyvinyl alcohol fiber is: The polyvinyl alcohol fiber, maleic anhydride and an esterification catalyst are mixed in a solvent and reacted; Preferably, the mass ratio of the polyvinyl alcohol fiber to maleic anhydride is (5-7):(3-5); Preferably, the reaction temperature is 90-100°C and the reaction time is 8-12h.
9. The easily roughened electroplated PC / ABS alloy material according to claim 8, It is characterized in that The esterification catalyst is selected from one or more of p-toluenesulfonic acid, thionyl chloride, and trifluoromethanesulfonic acid; Preferably, the esterification catalyst is used in an amount of 0.1-0.3% of the total mass of the polyvinyl alcohol fiber and maleic anhydride; Preferably, the solvent is one or more of DMF, dichloromethane and chloroform.
10. Use of the easily roughened electroplated PC / ABS alloy material according to any one of claims 1 to 5 or the easily roughened electroplated PC / ABS alloy material obtained by the method according to any one of claims 6 to 9 in automobile parts.
Citation Information
Patent Citations
Easily-electroplated electroplating PC (polycarbonate) / ABS (acrylonitrile butadiene styrene) alloy material and preparation method thereof
CN103602053A
PC / ABS material with high binding force and easy to electroplate and preparation method thereof
CN106633763A
Low-internal-stress electroplating-grade PC / ABS alloy material and preparation method thereof
CN111117195A
